Development of intercultural communicative competence. Challenges and contributions for the training of health professionals - Beltrán-Véliz, Juan; Gálvez-Nieto, José Luis; Klenner Loebel, Maura; Alarcón, Ana María; Vera-Gajardo, Nathaly (Acta Bioethica, 2025)
This paper reflects on intercultural communicative competence as a contribution to the training of professionals in health sciences. A reductionist, technocratic and culturally decontextualized health model is visualized, and the scarce development of "intercultural communicative competence" in health professionals is seen as a great barrier, which hinders communication with patients from other cultures. Therefore, it is vitally important to develop this competence in the training of these professionals. This will imply developing components that underlie this competence, that is, awareness, sensitivity and intercultural efficacy, which will allow the acquisition of cognitive, affective and behavioral skills that benefit effective and appropriate communication with patients from diverse cultural and social contexts. Likewise, they will allow them to understand in depth aspects, values and practices that underlie a culturally different health system, and will promote the advancement in the knowledge, understanding and development of innovative and relevant practices in the health system, from an intercultural and comprehensive approach. Finally, it will make it possible to overcome inequalities, misunderstandings, prejudices, exclusions and social injustices.